Penentuan Nilai Saham Terbaik Dalam Sistem Pendukung Keputusan Dengan Menggunakan Metode Simple Additive Weighting (SAW) - Edward Robinson Siagian (Bulletin of Information Technology (BIT), 2023)
In the current era of information technology, aspects of life have become dependent on the era of globalization, especially for business people. To support the economy, investment is an important step that must be taken. Generally, basic principles are needed to decide on investment steps in the form of shares in order to obtain maximum profits. The value of investing in the capital market requires sufficient information, experience, and business sense to analyze which investments to buy, which to sell, and which to keep. The value of shares is difficult for investors to predict with potential shares, so investors need to carry out investment trend analysis and for companies to first determine their investment policy model so that they make investment decisions in accordance with what is most expected with the level of risk tolerance limits. Analysis of investment information is useful for determining the value of the shares to be selected and to find out the expected rate of return to determine the investment strategy that will be carried out. Making decision support using several criteria that will be part of the strategy in determining potential shares. A decision support system is a decision that can help, speed up and simplify the decision making process. Fuzzy Multi-Attribute Decision Making (FMADM) with the Simple Additive Weighting (SAW) method is a method that can assist in making decisions regarding several alternative decisions that must be taken with several criteria that will be taken into consideration.